2004
DOI: 10.3390/ijerph2004010021
|View full text |Cite
|
Sign up to set email alerts
|

Liver and Renal Function Tests in Artisans Occupationally Exposed to Lead in Mechanic Village in Nnewi, Nigeria

Abstract: Additives in petroleum solvents have been reported to have adverse health implications. An evaluation study on some toxicological effects of occupational exposure to petroleum products (especially petrol which contains tetraethyl lead) amongst twenty five occupationally exposed artisans and twenty five graduate students of College of Health Sciences, Nnamdi Azikiwe University, Nnewi, Nigeria as controls, was carried out using the following biochemical markers: electrolytes, urea, uric acid, inorganic phosphoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
57
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 16 publications
13
57
9
Order By: Relevance
“…The obtained results of this study were further substantiated by previous studies that were conducted by Mikhail, et al [23,17,10] . Comparison between blood total bilirubin, direct bilirubin and in direct bilirubin concentrations in exposed and control sample in different cities in Sudan is shown in table (4).…”
Section: Biochemical Parameterssupporting
confidence: 80%
“…The obtained results of this study were further substantiated by previous studies that were conducted by Mikhail, et al [23,17,10] . Comparison between blood total bilirubin, direct bilirubin and in direct bilirubin concentrations in exposed and control sample in different cities in Sudan is shown in table (4).…”
Section: Biochemical Parameterssupporting
confidence: 80%
“…This is in contrast to Dioka et al (2004), who reported that occupational lead exposure did not have any effect on electrolytes, urea and creatinine levels. Plasma urea and creatinine are the most sensitive biochemical markers used in the assessment of renal tissue damage, because urea and creatinine are excreted through the kidneys.…”
Section: Discussioncontrasting
confidence: 53%
“…The albumin level in group F (MO+ Pb) was significantly lower compared to group C (MO), D (Pb) and the control group. The effect of lead exposure on the serum protein levels is controversial; Dioka et al (2004), Pachathundikandi et al (2006), andHerman et al (2009) observed no change in serum albumin level in automobile workers and albino rats exposed to long-term moderate lead concentrations. Histological and histochemical results of this study clearly support earlier reports that, lead has nephrotoxic effect on renal tissue and lead poisoning is associated with oxidative stress in blood and brain tissues (Adewole and Ayoka, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…7 Previous research provides a definite proof that exposure to lead causes significant adverse effects to multiple organ systems like Nervous, Haematological, Renal and Reproductive systems but very few human studies have been conducted to know the effect of lead on liver functions. 8 There is no available data to know the ill-effects of lead on liver functions in Indian scenario. Since liver is the major organs of storage, biotransformation and detoxification of lead we wanted to evaluated the toxic effects of this metal on liver functions.…”
Section: Introductionmentioning
confidence: 99%